The Role of the Iron Protoporphyrins Heme and Hematin in the Antimalarial Activity of Endoperoxide Drugs - Helenita C. Quadros; Mariana C. B. Silva; Diogo R. M. Moreira (MDPI AG, 2022)
Plasmodium has evolved to regulate the levels and oxidative states of iron protoporphyrin IX (Fe-PPIX). Antimalarial endoperoxides such as 1,2,4-trioxane artemisinin and 1,2,4-trioxolane arterolane undergo a bioreductive activation step mediated by heme (FeII-PPIX) but not by hematin (FeIII-PPIX), leading to the generation of a radical species. This can alkylate proteins vital for parasite survival and alkylate heme into hematin-drug adducts. Heme alkylation is abundant and accompanied by interconversion from the ferrous to the ferric state, which may induce an imbalance in the iron redox homeostasis. In addition to this, hematin-artemisinin adducts antagonize the spontaneous biomineralization of hematin into hemozoin crystals, differing strikingly from artemisinins, which do not directly suppress hematin biomineralization. These hematin-drug adducts, despite being devoid of the peroxide bond required for radical-induced alkylation, are powerful antiplasmodial agents. This review addresses our current understanding of Fe-PPIX as a bioreductive activator and molecular target. A compelling pharmacological model is that by alkylating heme, endoperoxide drugs can cause an imbalance in the iron homeostasis and that the hematin-drug adducts formed have strong cytocidal effects by possibly reproducing some of the toxifying effects of free Fe-PPIX. The antiplasmodial phenotype and the mode of action of hematin-drug adducts open new possibilities for reconciliating the mechanism of endoperoxide drugs and for malaria intervention.